The potential of targeting Ras proteins in lung cancer. (April 2015) - McCormick, Frank
<x xml:space="preserve">Abstract</x> The Ras pathway is a major driver in lung adenocarcinoma: over 75% of all cases harbor mutations that activate this pathway. While spectacular clinical successes have been achieved by targeting activated receptor tyrosine kinases in this pathway, little, if any, significant progress has been achieved targeting Ras proteins themselves or cancers driven by oncogenic Ras mutants. New approaches to drug discovery, new insights into Ras function, new ways of attacking undruggable proteins through RNA interference and new ways of harnessing the immune system could change this landscape in the relatively near future.